SPE International Symposium on Oilfield Chemistry 2015
DOI: 10.2118/173755-ms
|View full text |Cite
|
Sign up to set email alerts
|

Improved Fluid Technology for Stimulation of Ultrahigh-Temperature Sandstone Formation

Abstract: Acid stimulation is one of the production enhancement methodologies applicable in both development and exploration fields. Sandstone acidizing requires a sophisticated and well-studied approach to avoid formation damage caused by acid precipitation. Although the industry has made significant technical advancements in treatment fluids over the past decades, high bottomhole temperature still presents one of the biggest challenges. A new chelant-based fluid system was tailored to stimulate sandston… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Another chelant-based fluid system was tested by Rignol et al (2015) to stimulate sandstone core at 375 °F, which is an ultrahigh-temperature environment. This acid system was a combination of low-pH chelant and fluroboric acid, HBF 4 .…”
Section: Chelating Agentsmentioning
confidence: 99%
“…Another chelant-based fluid system was tested by Rignol et al (2015) to stimulate sandstone core at 375 °F, which is an ultrahigh-temperature environment. This acid system was a combination of low-pH chelant and fluroboric acid, HBF 4 .…”
Section: Chelating Agentsmentioning
confidence: 99%
“…Wormholes can be formed by EDTA and HEDTA at temperatures up to 400°F. Frenier and Hill (2002) and Mahmoud et al (2011) used chelating agent Reyes et al (2015), Rignol et al (2015) and found it effective in increasing sandstone permeability at high temperatures. It is highly admirable that many researches had focused on the development of acids which can be applied in hightemperature reservoirs.…”
Section: Chelating Agentsmentioning
confidence: 99%